Model of corporate social responsibility management in a quasi-public sector company of the republic of Kazakhstan - Bekenov, N. О.; Dossova, S. N. (Journal of Economic Research & Business Administration, 2022)
The authors substantiate the human factor in the management of corporate social responsibility (CSR) in the quasi-public sector of the economy. The purpose of the study: to identify patterns between the quality of CSR management in a quasi-public sector company and the level of CSR managers competence. The development of CSR at the level of a single quasi-public sector company is a complex, ambiguous, but very relevant and in-demand task for the Kazakhstan Republic. In practice, CSR is implemented in the format of projects (programs, initiatives), the effectiveness of which depends on the external and internal environment factors. One of the most significant is the human factor, manifested in the competencies and involvement of personnel involved in CSR projects. However, the influence of the human factor on the effectiveness of CSR projects remains poorly understood. The present study is aimed at filling this gap. Therefore, the designated topic of work is relevant. The question of managers' competencies in relation to CSR (research gap) remains open. That is, the question of what competencies managers developing CSR should have is subject to elaboration. Research methodology: general scientific methods of cognition: comparison, analysis and synthesis. In the applied part of the work, the method of correlation analysis using computer data processing tools, as well as the method of expert assessments, was used. A model for assessing the quality of CSR management in the format of BSC-metrics for fulfilling CSR management tasks has been developed. An analysis of the competences of CSR management was carried out on the example of CSR projects of a company in the quasi-public sector. A correlation analysis was carried out between the degree of fulfillment of CSR management tasks and the average score for the sum of all significant competencies of CSR management. The value of the study is that a close direct correlation has been established between the degree of fulfillment of CSR management tasks and the competencies of responsible CSR management. This can be applied to solve applied problems of managing CSR projects. Keywords: quasi-public sector, corporate social responsibility, corporate social responsibility management, principles of corporate social responsibility, CSR manager, CSR manager competencies